Visibility and the Policing of Public Space - Cook, Ian (Geography compass, 2011)
From studies of ‘panoptic’ CCTV surveillance to accounts of undercover police officers, it is often mooted that visibility and invisibility are central to the policing of public space. However, there has been no comprehensive and critical assessment of this axiom. Drawing on the practices of a variety of policing providers and regulators, and the work of geographers, criminologists and other social scientists, this paper examines how and why visibility underpins the policing of public space. We begin by considering the ways in which policing bodies and technologies seek to render themselves selectively visible and invisible in the landscape. The paper then moves on to explore the ways in which policing agents attempt to make ‘incongruous’ bodies, behaviours and signs variously visible and invisible in public space. We then offer a sympathetic critique of these accounts, arguing that more attention is needed in understanding: (i) how other senses such as touch, smell and sound are socially constructed as in and out-of-place and ‘policed’ accordingly; and (ii) how the policing of undesirable bodies and practices is not simply about quantitative crime reduction, but conducted through qualitative, embodied performance. The paper concludes by pinpointing key areas for future research